2013
DOI: 10.5194/acpd-13-26893-2013
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Uncertainties in future climate predictions due to convection parameterisations

Abstract: In the last decades several convection parameterisations have been developed to consider the impact of small-scale unresolved processes in Earth System Models associated with convective clouds. Global model simulations, which have been performed under current climate conditions with different convection schemes, significantly differ among each other in the simulated transport of trace gases and precipitation patterns due to the parameterisation assumptions and formulations, e.g. the simplified treatment… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Simulation quality related to time step is a model development issue and beyond the scope of the present paper, as is a more extensive intercomparison among different convective schemes for simulation characteristics related to model resolution. However, model uncertainties due to convective parameterization often revolve around the computation of mass fluxes, detrainment levels, and trigger functions, [ Rybka and Tost , ; Donner et al ., ].…”
Section: Mean Precipitationmentioning
confidence: 99%
“…Simulation quality related to time step is a model development issue and beyond the scope of the present paper, as is a more extensive intercomparison among different convective schemes for simulation characteristics related to model resolution. However, model uncertainties due to convective parameterization often revolve around the computation of mass fluxes, detrainment levels, and trigger functions, [ Rybka and Tost , ; Donner et al ., ].…”
Section: Mean Precipitationmentioning
confidence: 99%
“…General circulation models (GCMs) are widely used for global weather forecasting and climate modeling. In a GCM, the convective parameterization, which represents the bulk effects of convection, is typically regarded as a large source of model uncertainty (Arakawa, 2004; Rybka & Tost, 2014; Tost et al., 2006). Cumulus convection interacts with other processes in complex ways.…”
Section: Introductionmentioning
confidence: 99%
“…Various comparative studies have analysed climate models and concluded that a single best climate model does not exist (Dai, 2006; Stocker et al ., 2013; Jacob et al ., 2014; Rajczak and Schär, 2017; Vanden Broucke et al ., 2018). For a specific location, variable and season, the skill of different climate models and the climate change signals deviate among the models due to differences in spatial resolution (Anstey et al ., 2013; Watterson et al ., 2014; Mendoza et al ., 2016; Davini et al ., 2017; Hartung et al ., 2017), initial climatic conditions representing the internal variability of the climate system (Deser et al ., 2012; Fadhel et al ., 2017; Hosseinzadehtalaei et al ., 2017), parametrization schemes (Arakawa, 2004; Rybka and Tost, 2014; Prein et al ., 2015) and model components (Pitman, 2003; Lorenz et al ., 2012; Alexander and Easterbrook, 2015). Besides climate model differences, similarities arise from shared coding, the process of continuous model improvements and the fact that they all represent the same climate system (Masson and Knutti, 2011; Pennell and Reichler, 2011; Knutti et al ., 2013; Sunyer et al ., 2013; Leduc et al ., 2016).…”
Section: Introductionmentioning
confidence: 99%